Design of Quick Wins Based Policy for Facilitation and Assistance of Micro, Small, Medium Enterprises (MSMEs ) - Dina Suryawati; Alfareza Firdaus; Supranoto Supranoto (Magister Ilmu Administrasi Publik, 2023)
This research builds a conception of MSME policy as an important alternative to growing the economy in Indonesia. MSMEs in Indonesia are currently undergoing a phase of surviving the global crisis, so there are still many quick steps that the government must take. One step that needs to be taken is to build a fast and adaptive bureaucratic managerial pattern. This research focuses on constructing bureaucratic management based on quick wins as one of the principles of agile governance. In Indonesia, the concept of quick wins has a different scope from quick wins in agile governance. Quick wins in Indonesia tend to emphasize organizational and human resource management. Meanwhile, the conception of quick wins in agile governance focus on implementing an adaptive bureaucratic ecosystem to achieve maximum results. In order to build a conception of quick wins that focuses on the application of an adaptive bureaucratic ecosystem, this research uses Soft System Methodology (SSM), which can construct an appropriate conceptual building. The results of this study show that efforts to realize quick wins that focus on adaptive bureaucratic ecosystems involve revamping MSME policy management. Three elements that can drive the internal ecosystem of the organization toward realizing the concept of quick wins are visionary leaders, collaborative work patterns between teamwork and leaders, and organizational culture and resources.